Bach's testament : on the philosophical and theological background of The Art of Fugue - Göncz, Zoltán (Contextual Bach studies ;, 2013)
In Bach's Testament: On the Philosophical and Theological Background of The Art of Fugue, Göncz probes the philosophic-theological background of The Art of Fugue, revealing the special structures that supported the 1993 reconstruction. Bach's Testament investigates the reconstruction's metaphysical dimensions, focusing on the quadruple fugue. As a summary of Zoltán Göncz's extensive research over many years, which resulted in the completion of the fugue, this work explores the complex combinatorial, philosophical and theological considerations that inform its structure. Bach's Testament is ide.